Patterns and Predictors of Mental Health Service Utilization in People With Parkinson's Disease - Troeung, Lakkhina; Gasson, Natalie; Egan, Sarah (Sage Publications, 2014)
Comorbid psychiatric complications are a common occurrence in Parkinson’s disease (PD). However, the majority of people with PD experiencing mental health problems do not receive any professional treatment. Method: A total of327 Australian adults with PD completed a cross-sectional survey examining patterns of mental health service utilization and predictors of willingness to seek future mental health treatment. Results: Only 8% of participants were currently engaged in mental health treatment despite elevated levels of depressive and anxiety symptoms. The lifetime service use rate was also low at 24%. Logistic regression analysis showed that, second to prior treatment experience (odds ratio [OR] = 3.28, 95% confidence interval [CI] = 1.46-7.35), having had a discussion about psychological symptoms with a primary PD neurologist was the next most important predictor and tripled the likelihood of an individual being willing to seek future treatment, (OR = 3.01, 95% CI = 1.72- 5.27). Conclusion: This study highlights the integral role of the PD neurologist in facilitating awareness and treatment of mental health problems for individuals with PD.